Analysis of Airline Passenger Satisfaction Using the Rough Set Method - Alisa Putri Amanda Nasution; Auralia Izmi; Aprillya Zahra Iswandy Lubis; Haya Atiqah Tampubolon; Victor Asido Elyakim P (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2025)
This study analyzes airline passenger satisfaction using the Rough Set method, an effective approach in handling complex data without requiring additional information such as probability. The main factors influencing customer satisfaction are identified based on data collected through questionnaires and analyzed using the attribute reduction method. The results show that flight punctuality, cabin crew service quality, and flight class type have a significant influence on customer satisfaction. From the survey results, 72% of respondents stated that they were satisfied, 18% were quite satisfied, and 10% were dissatisfied, with dissatisfaction generally related to flight delays and lack of comfortable facilities. The application of the Rough Set method has been proven to be able to identify passenger satisfaction patterns more accurately, so that it can be used by airlines to improve their service strategies.